2002
DOI: 10.1016/s0009-2614(02)00520-1
|View full text |Cite
|
Sign up to set email alerts
|

29Si and 17O (Q)CPMG-MAS solid-state NMR experiments as an optimum approach for half-integer nuclei having long T1 relaxation times

Abstract: 29 Si up to 37 h were saved compared to the MAS experiment using longer recycle periods (up to 3600 s) but fewer scans. The spectrum reconstructed from the echoes provides similar spectral information as the MAS spectrum. In the 17 O spectrum increased sensitivity facilitated determination of CSA in a-quartz at 9.4 T and points towards a method to obtain natural abundance 17 O spectra of non-cubic oxides. Ó

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 14 publications
(21 reference statements)
2
53
0
Order By: Relevance
“…Because glasses display inhomogeneously broadened lines, the free induction decay (FID) dies out quickly, but the signal can be refocused by a train of refocusing pulses, allowing for the collection of the signal over a much longer time, which results, in turn, in an increased sensitivity. In the case of inhomogeneous line broadening due to quadrupolar interactions in crystals, it has been shown that the collection of such an echotrain can increase sensitivity by an order of magnitude [11][12][13]. Also, an increase in sensitivity by a factor of 3 in the 29 Si NMR spectra of zeolites [14] has been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because glasses display inhomogeneously broadened lines, the free induction decay (FID) dies out quickly, but the signal can be refocused by a train of refocusing pulses, allowing for the collection of the signal over a much longer time, which results, in turn, in an increased sensitivity. In the case of inhomogeneous line broadening due to quadrupolar interactions in crystals, it has been shown that the collection of such an echotrain can increase sensitivity by an order of magnitude [11][12][13]. Also, an increase in sensitivity by a factor of 3 in the 29 Si NMR spectra of zeolites [14] has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained spectra in the latter study however were distorted due to different T2 relaxation times for different sites. In addition, CPMG echotrains have been applied to collect the 29 Si NMR spectra of radiation-damaged zircons [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The sample mass was 90 mg in average. 29 Si/ 1 H CP-MAS NMR spectra were collected using contact times ranging from 2-8 ms. 29 Si MAS NMR spectra were acquired, using the Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence 40 with a recycle delay ranging from 2 s for altered samples, which were found to relax faster owing to protons, and 20 s for pristine glasses.…”
mentioning
confidence: 99%
“…Larsen and Farnan (46) were the first to use the CPMG pulse sequence as a method of increasing the receptivity of the NMR experiment for spin-1/2 nuclei. More recently, we and others have shown that the CPMG technique can give significant S/N enhancements for spin-1/2 nuclei having broad powder patterns, such as 109 Ag,113 Cd, 195 Pt, 199 Hg, and 207 Pb, while retaining anisotropic magnetic shielding information (47,48).…”
Section: Application Of Multiple-pulse Spin-echo Experiments: Spin-1/mentioning
confidence: 99%